2011
DOI: 10.15420/articles/endurance-sport-activity-and-risk-atrial-fibrillation-epidemiology-proposed-mechanisms-and
|View full text |Cite
|
Sign up to set email alerts
|

Endurance Sport Activity and Risk of Atrial Fibrillation – Epidemiology, Proposed Mechanisms and Management

Abstract: Although atrial fibrillation (AF) is considered the most common arrhythmia in clinical practice, its prevalence is relatively low in the young and middle-aged, ranging from 0.5 % in men below 40 years to 1 % by 60 years.1,2 Regular exercise is proposed as a powerful tool for the primary and secondary prevention of cardiovascular disease, reducing most of the risk factors that predispose to AF, such as hypertension, diabetes mellitus, coronary artery disease and obesity.3,4 However, there is growing evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Finally, although some evidence regarding atrial anatomic adaptations was reported by Müssigbrodt et al 1 and by Fragakis et al 8, alterations in autonomic nervous system, chronic systematic inflammation and fibrosis have been proposed as potential mechanisms for paroxysmal SVT induced by endurance exercise 2 5 8. However, this hypothesis is speculative.…”
Section: Descriptionmentioning
confidence: 97%
“…Finally, although some evidence regarding atrial anatomic adaptations was reported by Müssigbrodt et al 1 and by Fragakis et al 8, alterations in autonomic nervous system, chronic systematic inflammation and fibrosis have been proposed as potential mechanisms for paroxysmal SVT induced by endurance exercise 2 5 8. However, this hypothesis is speculative.…”
Section: Descriptionmentioning
confidence: 97%